PENERAPAN MODEL PROBLEM BASED LEARNING MELALUI GERAKAN MENULIS TEGAK BERSAMBUNG DI KELAS IIIC SDN REJOSARI 01 - Arum Destari; Kartinah; Endang Wuryandini; Mintyas Budiastuti (STKIP Subang, 2023)
This study aimed to illustrate how the Problem Based Learning model was implemented using cursive writing movements in class IIIC SDN Rejosari 01. It examined the student learning activities in class. The type of research used is descriptive qualitative research. Data collection techniques in this study include the observation and documentation stages. The results revealed that the Problem Based Learning model applied through cursive writing movements improved concentration and stimulated brain development in Class IIIC SDN Rejosari 01. Based on the results got by the students, it was explained that the application of the Problem Based Learning model through cursive writing movements can help students focus more on understanding the material.